Anxiolytic effect of YangshenDingzhi granules: Integrated network pharmacology and hippocampal metabolomics - Lv, Shimeng; Dai, Weibo; Zheng, Yan; Dong, Ping; Yu, Yihong; Zhao, Yifan; Sun, Shiguang; Bi, Dezhong; Liu, Chuanguo; Han, Fabin; Wu, Jibiao; Zhao, Tingting; et al. (Frontiers in Pharmacology, 2022)
Anxiety disorder is one of the most common mental diseases. It is mainly characterized by a sudden, recurring but indescribable panic, fear, tension and/or anxiety. Yangshendingzhi granules (YSDZ) are widely used in the treatment of anxiety disorders, but its active ingredients and underlying mechanisms are not yet clear. This study integrates network pharmacology and metabolomics to investigate the potential mechanism of action of YSDZ in a rat model of anxiety. First, potential active ingredients and targets were screened by network pharmacology. Then, predictions were verified by molecular docking, molecular dynamics and western blotting. Metabolomics was used to identify differential metabolites and metabolic pathways. All results were integrated for a comprehensive analysis. Network pharmacology analysis found that Carotene, β-sitosterol, quercetin, Stigmasterol and kaempferol in YSDZ exert anxiolytic effects mainly by acting on IL1β, GABRA1, PTGS1, ESR1, and TNF targets.Molecular docking results showed that all the affinities were lower than -5 kcal/mol, and the average affinities were -7.7764 kcal/mol. Molecular dynamics simulation results showed that RMSD was lower than 2.5 A, and the overall conformational changes of proteins were small, indicating that the small molecules formed stable complexes with proteins.The results of animal experiments showed that YSDZ exerts anxiolytic effects by regulating GABRA1 and TNF-α, ameliorating pathological damage in hippocampal CA1, and regulating metabolic pathways such as thiamine, cysteine and methionine metabolism, lysine biosynthesis and degradation. Altogether, we reveal multiple mechanisms through which YSDZ exerts its anti-anxiety effects, which may provide a reference for its clinical application and drug development.